Small for gestational age and obesity related comorbidities - Yong Hee Hong; Sochung Chung (Korean Society of Pediatric Endocrinology, 2018)
Infant born small for gestational age (SGA) are at increased risk of perinatal morbidity, persistent short stature and metabolic alterations in later life. The result of SGA followed by rapid weight gain during early postnatal life has been associated with increased long-term risks for central obesity, insulin resistance, impaired glucose tolerance, type 2 diabetes, hypertension, increased fat mass, and cardiovascular disease. We should carefully monitor their weight during infancy and childhood to prevent excessive rates of weight gain. 'Healthy catch up growth' may decreased the risk of obesity-related comorbidities in SGA. Establishing the optimal growth patterns in SGA to minimize short- and long-term risks is important, and further studies will be needed. This review discusses recent studies concentrating on obesity-related morbidities in SGA infants that may provide insight into growth monitoring.